Is the Novum the Whole? - Elena Madrussan (University of Bologna, 2020)
What does define the Novum? Starting from this matter, raised by the article of Boselli edited on this Journal, the Author inquiries about the possibility of considering the a-priori a reliable scientific and cultural suggestion